Directional anxiety responses in elite and sub-elite young athletes: intensity of anxiety symptoms matters - Lundqvist, C.; Kenttä, G.; Raglin, J. S. (Scandinavian Journal of Medicine & Science in Sports, 2011)
The objective was to examine the differences in anxiety ratings of elite and sub-elite athletes when the relationship between intensity and direction scores of anxiety ratings is considered in analyses. Participants were 31 junior elite (Mean age: 17.7, SD=1.1) and 53 sub-elite (Mean age: 17.5, SD=1.1) cross country skiers and swimmers who completed the direction modified CSAI-2R before important competitions. Results showed that elite athletes rated a higher percent of items as facilitative to their performance whereas sub-elite athletes rated a higher percent of items as debilitative. No significant differences between the elite and sub-elite samples were displayed regarding rated direction scores of cognitive or somatic anxiety at moderate to high-intensity levels. A significant difference in facilitative anxiety ratings was displayed at a low anxiety intensity level (Z=-2.20, P<0.05). Outcome performance data showed no consistent congruence with athletes' anxiety direction ratings. The findings suggest that facilitative direction scores are a consequence of low anxiety intensity, possibly combined with high self-confidence levels. Directional anxiety researchers analyzing separate total scores of intensity and direction respectively, which is the traditional approach, may draw incorrect conclusions about the importance of facilitative ratings of anxiety symptoms.